What do Consumers Prefer for the Attributes of Virtual Reality Head-mount Displays - Seung Ho Yang; Changi Nam (International Telecommunications Society (ITS), 2018)
Recently, the consumer virtual reality(VR) industry has been established with the introduction of VR head-mount displays(HMDs) and many have expected VR to become the next generation platform. Despite the circumstances, the adoption of VR HMDs is slower than expected. To comprehend this matter, this study explored consumers' preference on the attributes of VR HMDs by implementing the conjoint analysis methodology and deriving the marginal willingness-to-pay(MWTP) of the attributes. Based on past literature and analysis of the product, six attributes were derived: Visualization, Accessories, Weight, Ergonomic Design, Number of Contents, and Price. The results indicate that the wearable aspect of the device is the most important. Implications for future developmental directions for VR HMDs are suggested based on the results.
Keywords: 330